Studies of ice physical properties in Russia and USSR (late XIXth century – 1940). Ice density and porosity - K. Е. Sazonov; К. Е. Сазонов (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2023)
The paper deals with studies conducted in Russia and USSR of ice density, a most important characteristic of ice, and spans a period from the late XIXth century to 1940. It is shown that Russian scientists started their investigations of ice density only around the end of the XIX century, and those studies were often performed with specific applications in mind, e. g. works by B.P. Veinberg and his disciples in Tomsk in 1911–1914. In the USSR, there was a revival of interest in this kind of studies in the late 1920s in connection with explorations of the polar seas. Density measurements were mainly performed by hydrostatic weighing. At the request of N.N. Zubov and I.I. Mesyatsev in 1927 V.V. Shuleikin invented a simple instrument to measure ice density without weighing samples. In the early 1930s, ice porosity became an important field of research aimed at finding the causes of variance of experimental data on ice density. Ice porosity and density were studied using innovative devices developed by V.V. Shuleikin and V.I. Arnold-Alyabiev, which allowed studying ice properties in expedition conditions. The device developed by Arnold-Alyabiev found widespread use in field studies. Ice density and porosity are closely related physical quantities, therefore measuring the porosity of ice allowed researchers to estimate its density. By the end of the 1930s the ice density measurements had developed into a standard procedure of ice studies, which was due in large measure to the plans devised at the All-Union Arctic Institute headed by B.P. Veinberg to investigate ice at polar stations, which also included ice density and porosity studies. В работе рассматривается развитие изучения в России и СССР (конец XIX в. – 1940 г.) важнейшей характеристики льда — его плотности. Показано, что российские ученые занялись изучением плотности льда лишь в самом конце XIX в., причем эти исследования часто проводились с прикладными целями, например работы Б.П. Вейнберга и его учеников в Томске в 1911–1914 гг. В СССР интерес к ...